2014
DOI: 10.1007/s10040-014-1160-y
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the response of fresh groundwater to climate and vegetation changes in coral islands

Abstract: International audienceIn coral islands, groundwater is a crucial freshwater resource for terrestrial life, including human water supply. Response of the freshwater lens to expected climate changes and subsequent vegetation alterations is quantified for Grande Glorieuse, a low-lying coral island in the Western Indian Ocean. Distributed models of recharge, evapotranspiration and saltwater phytotoxicity are integrated into a variable-density groundwater model to simulate the evolution of groundwater salinity. Mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 52 publications
2
47
1
1
Order By: Relevance
“…Relatively few studies have been conducted for small coral islands. These studies (Bailey, Khalil, & Chatikavanij, ; Chui & Terry, ; Comte, Join, Banton, & Nicolini, ; Ketabchi et al, ; Morgan & Werner, ; Terry & Chui, ) are summarized in Table . Studies for other oceanic islands (Holding & Allen, ; Mahmoodzadeh et al, ; Sulzbacher et al, ) also are included to provide a broader range of methodologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively few studies have been conducted for small coral islands. These studies (Bailey, Khalil, & Chatikavanij, ; Chui & Terry, ; Comte, Join, Banton, & Nicolini, ; Ketabchi et al, ; Morgan & Werner, ; Terry & Chui, ) are summarized in Table . Studies for other oceanic islands (Holding & Allen, ; Mahmoodzadeh et al, ; Sulzbacher et al, ) also are included to provide a broader range of methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…Comte et al () performed a numerical modelling study for Grande Glorieuse Island, a small (5 km 2 ) coral island in the Western Indian Ocean with a maximum elevation of 15 m above mean sea level. They constructed a three‐dimensional groundwater model of the island subsurface using the SEAWAT modelling code (Langevin, Thorne, Dausman, Sukop, & Guo, ) and imposed one future climate scenario (SLR: 0.35‐cm increase; rainfall: +3% annual average from current) to assess impact on groundwater resources.…”
Section: Introductionmentioning
confidence: 99%
“…ET 0 was estimated using the method of Grabarczyk, developed in Poland (Grabarczyk and Żarski, 1992), which gives evapotranspiration values somewhat lower The total evapotranspiration flux includes both evaporation from the soil surface and transpiration of water taken up by plant roots from deeper soil layers. Several studies (e.g., Comte at al., 2014;Kamps et al, 2008) reported that water uptake by vegetation is an important factor influencing groundwater resources of freshwater lenses. In order to account for this, we performed two series of simulations.…”
Section: Simulation Setupmentioning
confidence: 99%
“…In particular, in view of possible climate change, increased water demands and sea level rise, the development of freshwater lenses supplied with infiltrated rainwater on top of saline aquifers is a subject of intense research (e.g., Werner et al, 2013). A large number of contributions have focused on freshwater lenses in deltaic regions, as well as on islands, peninsulas, or sandbars located in tropical, arid, and temperate climatic zones (e.g., Comte et al, 2014;Contractor and Jenson, 2000;Chang et al, 2016;De Louw et al, 2011;Eeman et al, 2017;Holding and Allen, 2015;Houben and Post, 2016;Illangasekare et al, 2006;Jocson et al, 2002;Mahmoodzadeh et al, 2014;Sadurski et al, 1987;Sinclair et al, 2016;Stuyfzand, 2016;Sulzbacher et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation